Intertwining of caring and learning in care practices supported by a didactic approach. (July 2018) - Ekebergh, Margaretha; Andersson, Niklas; Eskilsson, Camilla
Abstract: This paper highlights how caring and learning interact and become an intertwined phenomenon. The analysis of the research findings from two studies, in which the interaction between caring and learning in two educational units was investigated, has been guided by a Reflective Lifeworld Research approach grounded in a lifeworld-oriented phenomenology. The analysis procedure was concluded in a synthesis of the interaction between caring and learning in a Dedicated Educational Unit (DEU) and a didactic method inspired by a lifeworld educational perspective has been developed. The results show that through trust and genuine meetings between patients and students caring and learning can converge and be intertwined. Both students and patients take an active role in the health process as well as the learning process. In order to achieve an intertwining process qualified supervision, care managers who take responsibility for a caring and learning environment and a consensus between the nursing school and the healthcare organization is required. The didactic method that can support the intertwining of caring and learning consists of three themes; genuine meetings, sensitivity for the patient's story and reflection in interaction. These themes are tools for the supervision. Highlights: Intertwining of caring and learning strengthened both the patient's health processes and the student's learning process. A reflective attitude enable the intertwining. Genuine meetings, Sensitivity for the patient's story, Reflection in interactionsupport the intertwining. Nursing school and health care organization have a mutual responsibility in the implementation of the didactic method.